Survey of mastery of basic skills of playing futsal in 15-17 year old futsal athletes - Mustofa Aji Prasetyo; Supriatna Supriatna; Taufik Taufik (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
This study aims to determine the level of physical condition of Vasco Futsal Academy players in Lamongan Regency. This research is a type of quantitative descriptive research. The subjects of this study were Vasco Futsal Academy players, totaling 20 people. The data collection process was taken using one FIK Jogja battery tes instrumen which included passing, dribbling, and shooting. Overall, the results of the Vasco Futsal Academy's basic futsal tes results showed 10% “very good”, 15% “good”, 40% “moderate” and 30% “poor”, and 5% “very poor”. The conclusion obtained in this study is that the level of mastery of the basic skills of playing futsal by Vasco Futsal Academy players generally shows sufficient results, which is indicated by 40% being in the "enough " category.